Designing Authentic Learning Activities in Islamic Higher Education: A Conceptual Paper - Ainusyamsi, Fadlil Yani (Jurnal Penelitian Pendidikan Islam, 2020)
Conceptually, authentic learning is believed to be able to improve the quality of education and learning in higher education. Through authentic learning, students are invited to recognize everyday experiences and then are constructed into meaningful knowledge. Authentic learning also offers learning traditions that are not always based on text. This research offers a genuine learning design in Islamic tertiary institutions. Through a search of current and credible research reports, this article has succeeded in developing authentic learning designs in Islamic tertiary institutions.